Synergistic Effect of Neutral Protease and Clostripain on Rat Pancreatic Islet Isolation. Issue 7 (July 2015) - Dendo, Mami; Maeda, Hiroshi; Yamagata, Youhei; Murayama, Kazutaka; Watanabe, Kimiko; Imura, Takehiro; Inagaki, Akiko; Igarashi, Yasuhiro; Katoh, Yasutake; Ebina, Masayuki; Fujimori, Keisei; Igarashi, Kazuhiko; et al.
<x xml:space="preserve">Abstract</x> Background Islet isolation currently requires collagenase, neutral protease and other components. Thermolysin (TL) from Bacillus thermoproteolyticus is the gold standard neutral protease. However, we speculated that neutral protease derived from Clostridium histolyticum (Ch; ChNP) would be biologically superior for islet isolation. Tryptic-like activity has also been reported to be important. Therefore, we focused on clostripain (CP), since it is one of the main proteases in Clostridium histolyticum which possesses tryptic-like activity. We then examined the synergistic effects of highly purified ChNP and CP on rat islet isolation. Methods The same amount of collagenase was used in all four groups (TL, ChNP, TL+CP and ChNP+CP; n = 12/group). The efficiency was evaluated by the islet yield and function. An immunohistochemical analysis, in vitro digestion assay for each enzyme component and evaluation of the activation of endogenous exocrine proteases during islet isolation were also performed. Results The islet yield of the TL group was significantly higher than that of the ChNP group (P < 0.01). The islet yield was dose dependently increased in the ChNP+CP group, but was decreased in the TL + CP group. The islet yield in the ChNP + CP group was significantly higher than that in the TL group, but their islet function was similar. Different specificities for laminin, especially laminin-511, were observed in the TL, ChNP, and CP groups. Conclusions Clostripain had a strong synergistic effect with ChNP, but not with TL. Therefore, ChNP and CP, in combination with collagenase derived from the same bacteria, may effectively increase the isolation efficiency without affecting the quality of islets.